Exploratory Study of Students’ Creative Mindset, Perceived Values of Open Educational Resources, and Flow - Hungwei Tseng; Mark Sciuchetti; Yingqi Tang (Open Praxis)
As the awareness, benefits, and adoption of Open Educational Resources (OER) in various fields have increased, so have efforts to conduct research on its impact on students learning behaviors, experience, and engagement. However, limited research has been conducted regarding the efficacy of using OER on students’ perceived enjoyment in learning and interactions with educational materials. This study aimed to examine the relationships between creative mindset, flow experience, and perceived values of OER among 88 online undergraduate students. First, results revealed that students who have a growth-oriented creative mindset are more likely to understand and embrace OER’s intrinsic worth. Their willingness to learn new things and creative thinking fit in nicely with the OER tenets of accessibility, cooperation, and ongoing development. In addition, students reporting higher flow levels—characterized by control, attention, curiosity, and intrinsic interest—perceived greater value in OER materials. This indicates that the design and implementation of OER should consider the content and how it interacts with users to maximize engagement and flow. These findings emphasize the importance of a strategic approach to OER integration for educators and institutions, focusing on both resource quality and pedagogical frameworks that support its use. Ensuring OER materials engage and foster creative, and growth mindsets can significantly enhance students’ learning experience and academic enjoyment.